Scenario-Based Dynamic Modeling for Urban Settlement Management - Hidayat, Janthy Trilusianthy; Apriyanto, Heri (Science and Technology Research Centre Universitas PGRI Semarang, 2025)
The growth of residential areas in peri-urban regions of metropolitan areas such as Jabodetabek demonstrates high complexity due to the dynamic interaction between population growth, land use, and environmental degradation. This study aims to develop a dynamic system-based simulation model using a scenario approach to analyze sustainable residential area management policies. The scenarios were developed consists of no intervention, pessimistic, moderate, and optimistic based on parameters such as local government commitment, regional capacity improvement, and the rate of incoming migration. The simulation results indicate that the optimistic scenario is the most effective in controlling population size (a reduction of 29.14%), limiting residential expansion (a 58.57% decrease in the settlement area ratio), and improving the quality of the physical environment (a 95.18% increase) by the year 2040. The findings recommend strengthening spatial planning policies through enhanced cross-sectoral coordination, vertical housing development, and migration control. Although the model has limitations due to its assumption of a fixed system and the exclusion of external dynamics, this research provides valuable insights for the development of dynamic system-based policies in the sustainable planning of complex metropolitan regions.